Quality Control of White Sweet Potato (Ipomoea batatas Linneaus) As Raw Material for Chili Sauce : Pengawasan Mutu Ubi Jalar Putih (Ipomoea batatas Linneaus) Sebagai Bahan Baku Saus Sambal - Rembulani, Jihan Cahya; Rahmadhia, Safinta Nurindra (Universitas Muhammadiyah Sidoarjo, 2023)
Quality control is one of the important factors in maintaining the consistency of the quality of a product. The activity of controlling the quality of raw materials to ensure the quality of raw materials. Quality control starts from the receipt of raw materials until the time the raw materials will be used. Quality is used to determine the level of consumer acceptance of the product. The quality of a product is strongly influenced by the quality of the raw materials of the product. Therefore, it is necessary to have quality standards for raw materials that function as parameters and limits for an acceptable raw material which will then be processed into a product. Supervision was carried out visually with parameters of color, texture, shape, and size of white sweet potato which was carried out for 8 days. The analytical method used is the descriptive method, check sheet, and Pareto diagram. The results of this study will be compared with the quality standard of sweet potato according to SNI 01-4493-1998. Based on the results of the study, it is known that the sweet potato quality standards are set in PD. Surabraja Putra is classified based on weight, namely B (> 500 g), R (300-500 g) and TO (> 250 g) on the condition that the sweet potato is not deformed, rotten, hollow, moldy, and there are no foreign objects (soil, stems, leaves, and litter). The quality standard of sweet potato weight is set in PD. Surabraja Puta has complied with the weight quality of sweet potatoes according to SNI 01-4493-1998. However, the weight range used by PD. Surabraja Putra is larger than the weight range of sweet potatoes according to SNI. Varieties of local sweet potatoes used as raw material for chili sauce in PD. Surabraja Putra are Eski, Gaul, Asban, Melati, Manohara, and White Ase from Kuningan and Majalengka. The most common sweet potato defect found was the eski variety with a percentage of 39% and a weight of 496 kg.